Open Source, ICT infrastructure and firm performance - Daniel Cerquera Dussán; Bettina Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper empirically studies the impact of the adoption of open source software (OSS) on firms' labor productivity and innovative behavior. Using a representative sample of German firms, the results show that the adoption of OSS operating systems for servers and general OSS applications has no impact on firm level labor productivity, while the adoption of OSS operating systems for PCs impacts labor productivity negatively. This result points to the costs associated with the implementation of open source software. Moreover, the analysis shows that the adoption of OSS operating systems for PCs has a positive effect on the value of introduced process innovations, suggesting efficiency gains by adopting a tailored ICT infrastructure. These benefits might explain the positive correlation observed between OSS operating systems for servers and PCs, and firms' R&D intensities.
Keywords: D21; L25; O32; 330; Open Source; Information and Communication Technologies; R&D Incentives; Innovation; Firm Level Data